(untitled) (Linguostylistic Studies, 2019)
The issue of literary and dialectal language interaction is a topical issue of theoretical and practical importance in modern linguistics. One of its aspects is the use of dialects in the artistic texts that influences the dynamics of style and general literary norms through the aesthetic function of the language. The elucidation of the author’s individual features of presenting the conversational language elements in the artistic texts contributes to creating a holistic picture of the tendencies in dialect-literary vocabulary interaction in general and modern trends in the development of language and literature, in particular. The interest of the writers of Podlasie (Republic of Poland) to the folk language clearly manifested itself in the 80s of the twentieth century. The young poets, the bearers of the Ukrainian dialects, to realize their distinctiveness from the Poles and Bielorussians began to seek self-expression in the artistic word, actualizing the features of the local dialect in their texts. Yurii Havryliuk supported the trend of creating literary works in Ukrainian using dialect elements. The source of the research are the poetic texts from the collection of Yurii Havryliuk “In a never-ending march”. The purpose of the study is to trace multilevel features of the Podlasie Ukrainian dialect in the works of Yurii Havryliuk. At the phonetic level, the poet is disposed to preserve the specificity of reflexion of the ancient and positional variants of modern vowel phonemes, differences in consonant phonemes loading, combinatorial sound changes. At the morphological level, the most prominent dialect phenomena are those connected with the peculiarities of the substitution of the nominal parts of language with verbs. The features of the morphemic composition of adverbs are also in the focus of the study. Yurii Havryliuk attempted to use certain dialect elements, or imitation of the dialect speech, in his works, written in a Podlasie dialect, and he did it so skillfully that the dialect sounds like a literary language. The texts represent the North Podlasie Ukrainian dialects in all their diversity and can be successfully used as a material for the dialect studies.